1986
DOI: 10.1083/jcb.103.3.985
|View full text |Cite
|
Sign up to set email alerts
|

The alteration of myosin isoform compartmentation in specific mutants of Caenorhabditis elegans.

Abstract: Abstract. Myosin isoforms A and B are located at the surface of the central and polar regions, respectively, of thick filaments in body muscle cells of Caenorhabditis elegans, whereas paramyosin and a distinct core structure comprise the backbones of these filaments. Thick filaments and related structures were isolated from nematode mutants that have altered thick filament protein compositions. These mutant filaments and their complexes with specific antibodies were studied by electron microscopy to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 21 publications
2
40
1
Order By: Relevance
“…Importantly, the temperature-sensitive alleles directly affect the function of the unc-54-encoded myosin heavy chain B. Suppression of the phenotype of temperaturesensitive unc-45 mutants by overproduction of myosin A required a background null for unc-54 (Venolia and Waterston, 1990). This result indicates that myosin B inhibits assembly of myosin-A-containing filaments in the background of an unc-45 mutant even though myosin A can functionally substitute for myosin B (Epstein et al, 1986). However, studies of the lethal unc-45 alleles clearly indicated that UNC-45 also interacts with myosin A and probably the pharyngeal muscle myosins C and D. The pharynges showed decreased pumping in all lethal unc-45 alleles whereas the maternally rescuable lethal allele unc-45(st604) phenotype is enhanced by myosin A overproduction in contrast to the usual suppression.…”
Section: Elegans Unc-45mentioning
confidence: 89%
“…Importantly, the temperature-sensitive alleles directly affect the function of the unc-54-encoded myosin heavy chain B. Suppression of the phenotype of temperaturesensitive unc-45 mutants by overproduction of myosin A required a background null for unc-54 (Venolia and Waterston, 1990). This result indicates that myosin B inhibits assembly of myosin-A-containing filaments in the background of an unc-45 mutant even though myosin A can functionally substitute for myosin B (Epstein et al, 1986). However, studies of the lethal unc-45 alleles clearly indicated that UNC-45 also interacts with myosin A and probably the pharyngeal muscle myosins C and D. The pharynges showed decreased pumping in all lethal unc-45 alleles whereas the maternally rescuable lethal allele unc-45(st604) phenotype is enhanced by myosin A overproduction in contrast to the usual suppression.…”
Section: Elegans Unc-45mentioning
confidence: 89%
“…First, at least in nematode, thick filament assembly requires both chaperone (Liu et al, 1997;Hutagalung et al, 2002) and additional thick filament 'core' proteins (Epstein et al, 1986;Liu et al, 1997;Barral and Epstein, 1999), which suggests that strict molecular equivalence is not necessary for myosin assembly into thick filaments. Second, although (at least in Limulus) thick filaments are not rigid rods (Xu et al, 1991), studies of vertebrate and invertebrate thick filaments have shown that native thick filaments are less flexible than reconstituted thick filaments composed of myosin alone or rope-like filaments such as actin or DNA, and that this rigidity may be due to the thick filaments having tubular cores of non-myosin proteins Barral and Epstein, 1999).…”
Section: 23mentioning
confidence: 99%
“…Proper thick filament assembly instead requires a chaperone protein (Liu et al, 1997;Hutagalung et al, 2002), which may also be a permanent, myosin B associated thick filament component (Ao and Pilgrim, 2000), and thick filament 'core' (Epstein et al, 1986;Liu et al, 1997) and other (Mercer et al, 2006) proteins including paramyosin (Epstein et al, 1987). Missense mutations in the globular head portion of the myosin heavy chain, including the ATP binding site, also disrupt thick filament structure.…”
Section: 23mentioning
confidence: 99%
“…Our observations point directly to the pathway that Epstein, Waterston and colleagues have presented for C. elegans thick filament assembly. It holds that the central bipolar region containing myosin A forms first, nucleating the polar elongation of the paramyosin core, which is then followed by the addition of myosin B to the polar arms (Epstein et al, 1985(Epstein et al, , 1986Waterston, 1989b). This pathway, combined with the structural and expression defects of mutations, is illustrated in Fig.·6.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of mutants in these genes, as well as information on the pathway of thick filament assembly, enabled us to investigate the interdependence of myosin and paramyosin synthesis. In these studies, we find a complex relationship between the expression of the major components of thick filaments -myosin A (myo-3), myosin B (unc-54) and paramyosin (unc-15) -that is best explained in terms of the pathway of thick filament assembly proposed by Epstein et al (1985Epstein et al ( , 1986.…”
Section: Discussionmentioning
confidence: 99%